PGE2-Induced IDO1 Inhibits the Capacity of Fully Mature DCs to Elicit an In Vitro Antileukemic Immune Response - Sara Trabanelli; Mariangela Lecciso; Valentina Salvestrini; Michele Cavo; Darina Očadlíková; Roberto M. Lemoli; Antonio Curti (Journal of Immunology Research)
In the last years, dendritic cells (DC) have been evaluated for antitumor vaccination. Although DC-based vaccines have raised great expectations, their clinical translation has been largely disappointing. For these results, several explanations have been proposed. In particular, the concomitant expression by DCs of tolerogenic pathways, such as the immunosuppressive agent indoleamine 2,3-dioxygenase-1 (IDO1), has been demonstrated. The aim of this study is to evaluate both the stimulatory and the tolerogenic feature of monocyte-derived DCs (Mo-DCs) after maturation with PGE2. In particular, the role of IDO1 expression in PGE2-matured Mo-DCs has been addressed. Here we show that PGE2, which is required for full maturation of DCs, is one mediator of DC tolerance by enhancing IDO1. PGE2-mediated expression of IDO1 results in the production of kynurenine, in the generation of Tregs, and in the inhibition of either the allogeneic or the autologous antigen-specific stimulatory capacity of DCs. When pulsed with leukemic lysates and matured with PGE2, DCs are impaired in the induction of IFN-γ secreting CD4+ and CD8+ T cells due to IDO1 upregulation. Moreover, the inhibition of IDO1 enhances the antileukemic response. Overall, these results point toward the use of IDO1 inhibitors to enhance the vaccination capacity of DCs, matured with PGE2.